PENGARUH GAYA KEPEMIMPINAN DAN BEBAN KERJA TERHADAP KEPUASAN KERJA PADA KARYAWAN PERUSAHAAN TAMBANG MINYAK NASIONAL (PERTAMINA) REFINERY UNIT IV CILACAP - Al Faqih, Muhammad Sabiq (Jurnal Kewirausahaan dan Inovasi, 2022)
This study aims to determine the effect of leadership style and workload variables on job satisfaction of employees of the National Oil Mining Company (PERTAMINA) Processing Unit IV Cilacap. The population of this quantitative descriptive research is 110 people and the sample is 52 people using the Slovin formula which from the number of samples taken can describe the condition of the original population. This study uses quantitative data in the form of primary data sources with survey data collection techniques using questionnaires. This study uses an instrument test through validity and reliability testing, classical assumption test through normality test, multicollinearity test, linearity test and heteroscedasticity test, the data analysis tool used is SPSS version 22. The results of the multiple linear regression analysis show that the variables of leadership style and workload has a positive and significant effect on employee job satisfaction